Sulfur vacancy modified indium zinc sulfide catalyst, preparation method and application thereof

CN122974337APending Publication Date: 2026-10-27KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611027423.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了解决现有硫化铟锌(ZnIn2S4)只能在光催化下合成H2O2,不能在暗环境下催化合成H2O2的问题,本发明的目的之一是提供了一种硫空位修饰的硫化铟锌催化剂的制备方法,所述方法的具体步骤为:

Benefits of technology

(1)仿生电子存储机制:在300~500℃煅烧阶段熔融的KSCN(硫氰化钾)形成一个高度流动的柔性溶剂笼,促进反应离子的横向扩散和二维各向异性生长,同时通过物理约束效应有效抑制晶体的堆叠和过度垂直生长,从而获得超薄纳米片结构;同时通过温度诱导硫原子逃逸,精确引入适当浓度的硫空位,硫空位成功模拟了自然光合作用中质体醌的电子存储功能,在N2饱和的三乙醇胺水溶液中,ZnIn2S4体系通过光致变色现象直接可视化光充电暗放电过程,为解耦光反应与暗反应提供了新的材料平台,可作为一种高效的产过氧化氢催化剂应用于清洁能源生产中,具有良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974337A_ABST
    Figure CN122974337A_ABST
Patent Text Reader

Abstract

The application relates to the field of catalytic materials and green energy production technology, and discloses a sulfur vacancy modified indium zinc sulfide catalyst and a preparation method and application thereof. The preparation method comprises the following steps: mixing zinc chloride, indium chloride and potassium thiocyanate, performing one-step calcination through molten salt dynamic confinement, and then performing washing and drying to obtain sulfur vacancy modified ultrathin ZnIn2S4 nanosheets (ZIS V ). ZIS V Can be excited by visible light to generate photo-generated electrons and holes, the photo-generated electrons can be stored in the sulfur vacancy, and the photo-generated electrons stored in the sulfur vacancy are automatically released under dark conditions and drive the reaction of oxygen and water under dark state to generate H2O2. ZIS V After irradiation for 40 minutes in a pure water system without a sacrifice agent, 0.10 mmol.g ‑1 of H2O2 can be generated under dark state; and after irradiation for 10 minutes with the assistance of ethanol, the yield under dark state is increased to 0.28 mmol.g ‑1 The dark light catalyst provided by the application has simple preparation process, is green and sustainable, can realize efficient H2O2 production under all-weather and intermittent light conditions, and has wide application prospect in the field of photocatalytic solar energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic materials and green energy production technology, specifically to a sulfur vacancy-modified indium zinc sulfide catalyst, its preparation method, and its application. Background Technology

[0002] Hydrogen peroxide (H2O2) is an environmentally friendly green oxidant and an emerging liquid fuel with broad application prospects in chemical synthesis, environmental protection, and energy conversion. Utilizing semiconductor photocatalysis technology and driven by solar energy to directly convert water and oxygen into H2O2 is an ideal green synthesis route.

[0003] However, traditional photocatalysis technology has a fundamental limitation: the photocatalytic reaction is heavily dependent on continuous light. Once the light stops (such as at night, on cloudy days, or in dim indoor conditions), the generation of photogenerated carriers immediately ceases, and H2O2 synthesis also stops. The inherent intermittent, diurnal, and regional characteristics of solar radiation pose a significant challenge to the continuous, all-weather production of H2O2.

[0004] Indium zinc sulfide (ZnIn2S4), as a ternary sulfide semiconductor, has attracted widespread attention in the field of photocatalysis due to its advantages such as visible light response, good chemical stability, and environmental friendliness. However, unmodified ZnIn2S4 suffers from problems such as rapid recombination of photogenerated carriers and lack of electron storage capacity, making it difficult to achieve sustained catalytic reactions in the dark. Summary of the Invention

[0005] To address the limitation that existing indium zinc sulfide (ZnIn2S4) catalysts can only synthesize H2O2 under photocatalysis and not in the dark, one objective of this invention is to provide a method for preparing a sulfur vacancy-modified indium zinc sulfide catalyst. The specific steps of this method are as follows: (1) Grind and mix the zinc source, indium source and potassium thiocyanate to obtain a precursor mixture.

[0006] (2) The obtained precursor mixture was calcined in an air atmosphere, and the solid obtained by the reaction was washed and dried to obtain sulfur vacancy modified indium zinc nanosheets.

[0007] Preferably, the molar ratio of zinc source to indium source in step (1) is 1:2; the molar and mass ratio of zinc source to potassium thiocyanate is 1:5, in mmol:g.

[0008] Preferably, the zinc source in step (1) is zinc chloride and the indium source is indium chloride.

[0009] Preferably, the calcination conditions in step (2) are to heat to 300-500°C at a heating rate of 1-10°C / min and hold for 2-6 hours.

[0010] The second objective of this invention is to provide a sulfur vacancy-modified indium zinc sulfide catalyst, which has the following characteristics: (1) The catalyst has reversible photochromic properties. Under visible light irradiation, the color of the ZnIn2S4 suspension changes from yellow to avocado green in a triethanolamine aqueous solution saturated with N2. After contact with oxygen in the dark, it returns to yellow, thus visualizing the photocharging and dark discharge processes. (2) The catalyst stores photogenerated electrons under light irradiation and releases electrons after the light irradiation stops.

[0011] The third objective of this invention is to provide an application of a sulfur vacancy-modified indium zinc sulfide catalyst in the preparation of hydrogen peroxide.

[0012] Compared with the prior art, the present invention has the following beneficial effects: (1) Biomimetic electronic storage mechanism: KSCN (potassium thiocyanate) melted during the calcination stage at 300-500℃ forms a highly fluid flexible solvent cage, which promotes the lateral diffusion of reactant ions and two-dimensional anisotropic growth. At the same time, the physical constraint effect effectively inhibits the stacking of crystals and excessive vertical growth, thereby obtaining an ultrathin nanosheet structure. Meanwhile, by inducing the escape of sulfur atoms through temperature, an appropriate concentration of sulfur vacancies is precisely introduced. The sulfur vacancies successfully simulate the electronic storage function of plastoquinone in natural photosynthesis. In N2-saturated triethanolamine aqueous solution, the ZnIn2S4 system directly visualizes photocharging through photochromic phenomena. The dark discharge process provides a new material platform for decoupling photo-reactions and dark-reactions, and can be used as a highly efficient hydrogen peroxide production catalyst in clean energy production, showing promising application prospects.

[0013] (2) All-weather catalytic capability: The catalyst not only produces H2O2 efficiently under light, but more importantly, it can continue to produce H2O2 by utilizing stored electrons after the light stops (night, cloudy, indoor dim light). This overcomes the fundamental defect of traditional photocatalysis that relies on continuous light, and has high practical value and good application prospects.

[0014] (3) Green and sustainable: Even in a pure water system without sacrificial agents, it still has the intrinsic ability to produce H2O2 in the dark state.

[0015] (4) Excellent performance: The yield of H2O2 under light without sacrificial agent and the yield in the dark are significantly better than those of ZnIn2S4 without vacancies. The high performance of the floating artificial blade under actual intermittent natural light conditions verifies its practical application potential.

[0016] (5) The preparation method is simple and controllable: sulfur vacancies can be introduced through the dynamic confinement effect of molten salt in one step. The preparation process is simple, low cost, and does not require complex equipment. The molten salt medium can be recycled and reused, which is in line with the concept of green chemistry. Attached Figure Description

[0017] Figure 1 The XRD patterns are of the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1.

[0018] Figure 2 The image shows the SEM image of the sulfur vacancy-modified indium zinc sulfide catalyst prepared in Example 1.

[0019] Figure 3 This is a TEM image of the sulfur vacancy-modified indium zinc sulfide catalyst prepared in Example 1.

[0020] Figure 4 The image shows the AFM test results of the sulfur vacancy-modified indium zinc sulfide catalyst prepared in Example 1.

[0021] Figure 5 The elemental distribution diagram is shown for the sulfur vacancy-modified indium zinc sulfide catalyst prepared in Example 1.

[0022] Figure 6 The images show the EDS spectra of the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1.

[0023] Figure 7 The graph shows the EPR test results of the sulfur vacancy-modified indium zinc sulfide catalysts obtained in Examples 1-3 and the sulfur vacancy-free pure indium zinc sulfide catalysts obtained in Comparative Example 1.

[0024] Figure 8 XPS images of the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1.

[0025] Figure 9 The figures show the photochromic phenomena of the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1.

[0026] Figure 10 The yield of H2O2 produced by the sulfur vacancy-modified indium zinc sulfide catalysts obtained in Examples 1-3, the sulfur-vacancy-free pure indium zinc sulfide obtained in Comparative Example 1, and the sulfur vacancy-containing indium zinc sulfide obtained in Comparative Example 2 under dark conditions in pure water is shown.

[0027] Figure 11The yield of H2O2 produced by the sulfur vacancy-modified indium zinc sulfide catalysts obtained in Examples 1-3, the sulfur-vacancy-free pure indium zinc sulfide obtained in Comparative Example 1, and the sulfur vacancy-containing indium zinc sulfide obtained in Comparative Example 2 under dark conditions in ethanol.

[0028] Figure 12 The yield of H2O2 in pure water after 40 minutes of light exposure and 3 minutes of darkness was obtained for the sulfur vacancy-modified indium zinc sulfide catalysts obtained in Examples 1-3, the sulfur-vacancy-free pure indium zinc sulfide obtained in Comparative Example 1, and the sulfur vacancy-containing indium zinc sulfide obtained in Comparative Example 2.

[0029] Figure 13 The yield of H2O2 in artificial leaves prepared by the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 under natural light.

[0030] Figure 14 A schematic diagram of the photocharging and dark discharge mechanism of H2O2 production from indium zinc sulfide prepared by the molten salt method. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1 A method for preparing a sulfur vacancy-modified indium zinc sulfide catalyst, the specific steps of which are as follows: (1) Weigh 2 mmol of ZnCl2, 4 mmol of InCl3 and 10 g of potassium thiocyanate according to the stoichiometric ratio and place them in an agate mortar. Grind and mix them evenly for 10 minutes to obtain a precursor mixture.

[0033] (2) The precursor mixture was transferred to a ceramic crucible, placed in a muffle furnace, heated to 400°C at a heating rate of 5°C / min, held for 4 hours, and then naturally cooled to room temperature. The obtained solid was washed three times with hot deionized water and twice with anhydrous ethanol to remove residual potassium thiocyanate. Finally, it was dried at 60°C for 12 hours to obtain a light yellow powder, which is the sulfur vacancy-modified indium zinc sulfide catalyst, labeled as ZIS. V .

[0034] The sulfur vacancy-modified indium zinc sulfide catalyst prepared in this embodiment was subjected to SEM analysis, and the results are as follows: Figure 2 As shown. By Figure 2 It can be seen that the catalyst exhibits a nanosheet morphology.

[0035] The sulfur vacancy-modified indium zinc sulfide catalyst prepared in this embodiment was subjected to high-resolution TEM (HRTEM) testing, and the results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the 0.33 nm lattice distance is attributed to the (100) and (010) crystal planes of the hexagonal ZnIn2S4. In the HRTEM image, it can be clearly seen that the lattice stripes are interrupted and blurred, and there is discontinuity, which is caused by sulfur vacancies.

[0036] The sulfur vacancy-modified indium zinc sulfide catalyst prepared in this embodiment was subjected to AFM testing, and the results are as follows: Figure 4 As shown. By Figure 4 It can be seen that ZIS V The average thickness of the nanosheets is around 5 nm, confirming their ultrathin nanosheet morphology.

[0037] The sulfur vacancy-modified indium zinc sulfide catalyst prepared in this embodiment was subjected to mapping elemental distribution testing, and the results are as follows: Figure 5 As shown. By Figure 5 It can be seen that the three elements Zn, In and S are evenly distributed on the nanosheet.

[0038] This embodiment presents a schematic diagram of the photocharging and dark discharge mechanism of the sulfur vacancy-modified indium zinc sulfide catalyst for H2O2 production. It illustrates the entire process of sulfur vacancy-containing indium zinc sulfide producing H2O2 in a two-stage light / dark cycle: Under light, the material is excited by light to generate photogenerated electron-hole pairs. On the one hand, photogenerated holes oxidize H2O and photogenerated electrons reduce O2 to simultaneously generate H2O2. On the other hand, sulfur vacancies act as deep-level traps to capture surplus photogenerated electrons and complete electron storage. After entering a dark environment, the electrons stored in the sulfur vacancies are slowly released, continuously driving the reaction with oxygen to stably generate H2O2 until the stored electrons are completely depleted, and the material returns to its initial state, thereby achieving all-weather photosynthesis of H2O2.

[0039] Example 2 The only difference between this embodiment and embodiment 1 is that in step (2), the temperature is increased to 300°C at a rate of 5°C / min; the other steps and parameters are the same as in embodiment 1.

[0040] Example 3 The only difference between this embodiment and embodiment 1 is that in step (2), the temperature is increased to 500°C at a rate of 5°C / min; the other steps and parameters are the same as in embodiment 1.

[0041] Comparative Example 1 As a control, pure zinc indium sulfide (ZIS) without sulfur vacancies was prepared using a conventional water bath method. The specific steps are as follows: 3 mmol of zinc acetate dihydrate, 6 mmol of indium chloride and 16 mmol of thioacetamide were dissolved in 500 mL of deionized water and stirred for 30 minutes. The mixture was then transferred to a water bath, heated to 95 °C and kept at that temperature for 5 hours with vigorous stirring. The precipitate was collected by centrifugation, washed several times with water and ethanol, and finally dried at 60 °C for 12 hours.

[0042] Comparative Example 2 As a control, the sulfur-vacancy-free pure indium zinc sulfide prepared in Comparative Example 1 was calcined at 250°C for 1 hour to prepare indium zinc sulfide with sulfur vacancies.

[0043] Performance testing Test Example 1 The sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the ordinary sulfur vacancy-free pure indium zinc sulfide catalyst obtained in Comparative Example 1 were analyzed by XRD, and the results are as follows: Figure 1 As shown. By Figure 1 It can be seen that the catalyst prepared in Comparative Example 1 exhibits characteristic diffraction peaks consistent with the standard spectrum of hexagonal ZnIn2S4 (JCPDS document number 65-2023), while the catalyst obtained in Example 1 exhibits diffraction peaks similar to those of ordinary ZIS, indicating that the introduction of S vacancies did not change the crystal structure of indium zinc sulfide.

[0044] Test Example 2 The sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the ordinary sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1 were subjected to EDS energy dispersive spectroscopy tests, and the results are as follows: Figure 6 As shown. By Figure 6 It can be seen that ZIS and ZIS V The atomic ratios of Zn / In / S in the samples were 1:1.92:4.32 and 1:1.93:3.68, respectively, confirming that Zn / In / S is a solid zinc oxide (ZIS) alloy. V There is a certain concentration of sulfur vacancies.

[0045] Test Example 3 The sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the ordinary sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1 were subjected to EPR tests, and the results are as follows: Figure 7 As shown. By Figure 7 It can be seen that ZIS does not exhibit EPR characteristic signals, while ZIS V A clear signal appears at g=2.004, indicating that ZIS V There is an empty space S.

[0046] Test Example 4 The sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 and the ordinary sulfur vacancy-free pure indium zinc sulfide obtained in Comparative Example 1 were subjected to photochromic phenomenon tests, and the results are as follows: Figure 9 As shown. By Figure 9 It can be seen that when ZIS is irradiated with visible light in a N2-saturated triethanolamine solution... V After dispersion, obvious reversible photochromic behavior was observed. The dispersion changed from the initial yellow to avocado green, which can be regarded as a photocharging process. After the light source was turned off and exposed to air (dark discharge process), it gradually returned to the original yellow color, indirectly visualizing the photocharging and dark discharge processes. ZIS did not show any photochromic phenomenon under the same conditions, indicating that S vacancies can store photogenerated electrons and release them in an oxygen-containing environment.

[0047] Test Example 5 The catalysts prepared in the examples and comparative examples were tested for H2O2 production performance in pure water under dark conditions. The test steps are as follows: Disperse 15 mg of catalyst in 30 mL of pure water, introduce oxygen into the system, and then apply the solution to a 10 W LED visible light source (light intensity 75 mW·cm²). -2 After irradiating for 40 minutes to perform photocharging, the light source was turned off, and the reaction was carried out in darkness for 3 minutes. Samples were then taken to measure the H2O2 concentration. The results are as follows: Figure 10 As shown, by Figure 10 It can be seen that the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 exhibits superior hydrogen peroxide production ability in the dark compared to the ordinary sulfur-vacancy-free pure indium zinc sulfide obtained in Comparative Example 1. The hydrogen peroxide yield of the sulfur vacancy-modified indium zinc sulfide catalyst obtained in Example 1 in the dark is 0.10 mmol·g. -1 The dark-light catalyst obtained in Example 3 produced a hydrogen peroxide yield of 0.09 mmol·g in the dark. -1 The dark-light catalyst obtained in Example 2 produced a hydrogen peroxide yield of 0.05 mmol·g in the dark. -1 Clearly, the prepared indium zinc sulfide catalyst with sulfur vacancies exhibited the best dark-state catalytic performance at a reaction temperature of 400℃, indicating that Example 1 possesses the best dark-state catalytic performance; while the catalyst prepared in Comparative Example 1 showed a hydrogen peroxide yield of 0 mmol·g in the dark. -1 Comparative Example 2 showed a hydrogen peroxide yield of 0.02 mmol·g in the dark. -1 The low amount of S-vacancies generated by calcination in indium zinc sulfide indicates that the S-vacancies introduced by the dynamic confinement effect of molten salt can store photogenerated electrons, which are released in the dark to drive the reaction to generate H2O2.

[0048] Test Example 6 The performance of H2O2 production in the dark state under ethanol-assisted conditions was tested in Examples 1-3 and Comparative Examples 1 and 2, respectively. The test steps are as follows: Disperse 15 mg of catalyst in 30 mL of ethanol aqueous solution (20 V%), introduce oxygen into the system, and then apply the solution to a 10 W LED visible light source (light intensity 75 mW·cm²). -2 The light source was irradiated for 10 minutes for photocharging, then the light source was turned off, and the reaction was carried out in darkness for 3 minutes. Samples were then taken to measure the H2O2 concentration. The results are as follows: Figure 11 As shown, the catalyst obtained in Example 1 exhibited superior hydrogen peroxide production capabilities in the dark compared to the catalyst obtained in the comparative example. The dark-light catalyst obtained in Example 1 increased the hydrogen peroxide yield to 0.28 mmol·g in the dark. -1 With the aid of ethanol, the recombination of photogenerated electrons and holes was suppressed, resulting in more photogenerated electrons being stored in S vacancies. Clearly, the prepared sulfur-vacancy-containing indium zinc sulfide dark-light catalyst exhibited the best dark-state catalytic effect at a reaction temperature of 400℃, indicating that Example 1 possesses the best dark-light catalytic performance. In contrast, the comparative example showed a hydrogen peroxide yield of 0 mmol·g in the dark. -1 This indicates that the S vacancies introduced by the dynamic confinement effect of molten salt can better store photogenerated electrons, which are released in the dark to drive the reaction to generate H2O2.

[0049] Test Example 7 The catalysts prepared in the examples and comparative examples were subjected to H2O2 production performance tests in pure water after 40 minutes of light irradiation followed by 3 minutes of darkness. The test steps are as follows: Disperse 15 mg of catalyst in 30 mL of pure water, introduce oxygen into the system, and then apply the solution to a 10 W LED visible light source (light intensity 75 mW·cm²). -2 The yield of H2O2 was tested by photocatalytic production under irradiation for 40 minutes. Afterwards, the light source was turned off, and the reaction was carried out in darkness for 3 minutes. Samples were then taken to measure the H2O2 concentration. The results are as follows: Figure 12 As shown, the catalysts obtained in the examples exhibited superior H2O2 yields compared to those obtained in the comparative examples under light irradiation without sacrificial agents. Specifically, Example 1 achieved a yield of 2.61 mmol·g after 40 minutes of irradiation. -1 Compared to control example 1, which showed only 0.32 mmol·g after 40 minutes of light exposure, control example 1 showed only 0.32 mmol·g. -1 After the light source was turned off and the area was in darkness for three minutes, the H2O2 production in Example 1 increased to 2.71 mmol·g. -1In contrast, Comparative Example 1 showed no increase in yield after three minutes in darkness. Compared to Comparative Example 2, Example 1 exhibited significantly improved photocatalytic and dark catalytic performance. This is attributed to the structural advantage of the molten salt dynamic confinement effect over the sulfur vacancies introduced by the traditional multi-step method: on the one hand, the sulfur vacancies induced by this strategy are more conducive to the separation of photogenerated electron-hole pairs and their participation in surface catalytic reactions; on the other hand, it allows more photogenerated electrons to be effectively stored in the catalyst and released in the dark to drive the synthesis of H2O2. Therefore, the molten salt dynamic confinement strategy is superior to the traditional multi-step method in both promoting charge separation and enhancing electron storage capacity, thus achieving a dual improvement in photocatalytic and dark catalytic performance. For details on the specific increases in yield for other samples under dark conditions, please refer to [link to relevant documentation]. Figure 10 As shown.

[0050] Test Example 8 Based on sodium alginate membrane technology, the composite membrane of Example 1 was successfully synthesized. Its photocatalytic H2O2 production performance was tested under intermittent outdoor natural sunlight irradiation by constructing a simple, freestanding artificial leaf (the film of Example 1). Figure 13 As shown, this solar photocatalytic system requires only pure water and the thin film from Example 1 to operate, and its floating characteristics constitute a simple three-phase interface system. Outdoor experiments showed that after 3 hours of intermittent natural sunlight irradiation (15:00–18:00, accompanied by cloudy and overcast weather), the H2O2 concentration in the system reached 8.5 mmol·g. -1 .

[0051] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a sulfur vacancy-modified indium zinc sulfide catalyst, characterized in that: The specific steps of the method are as follows: (1) Grind and mix the zinc source, indium source and potassium thiocyanate to obtain a precursor mixture; (2) The obtained precursor mixture was calcined in an air atmosphere, and the solid obtained by the reaction was washed and dried to obtain a sulfur vacancy modified indium zinc sulfide catalyst.

2. The method for preparing the sulfur vacancy-modified indium zinc sulfide catalyst according to claim 1, characterized in that: The molar ratio of zinc source to indium source in step (1) is 1:2; the molar and mass ratio of zinc source to potassium thiocyanate is 1:5, in mmol:g.

3. The method for preparing the sulfur vacancy-modified indium zinc sulfide catalyst according to claim 1, characterized in that: The zinc source in step (1) is zinc chloride, and the indium source is indium chloride.

4. The method for preparing the sulfur vacancy-modified indium zinc sulfide catalyst according to claim 1, characterized in that: In step (2), the calcination conditions are to heat to 300-500℃ at a heating rate of 1-10℃ / min and hold for 2-6 hours.

5. The sulfur vacancy-modified indium zinc sulfide catalyst prepared by the method according to any one of claims 1 to 4, characterized in that: The indium zinc sulfide catalyst contains sulfur vacancies.

6. The application of the sulfur vacancy-modified indium zinc sulfide catalyst of claim 5 in the preparation of hydrogen peroxide under light or no light conditions.